A Photo Voltaic Source Fed Novel Boosting Switched Z-Source Multilevel Inverter - Sinu KJ; G. Ranganathan (Institute of Advanced Engineering and Science, 2018)
This paper presents a new switched z-source multilevel inverter powered from a photovoltaic source. Addition of a power electronic switch in conventional z-source network provides excellent voltage boosting capability with moderate power rating which makes it suitable for low voltage photo voltaic applications. Proposed topology consists of single dc source, six power switches, two diodes, four capacitors and two inductors comparing to conventional five level schemes proposed topology contains less number of switches and passive elements. This scheme produces voltage waveform with lesser harmonics and shows lesser THD percentage by using different modulation index of multi carrier level shifted PWM technique. Proposed switched z-source multilevel inverter is implemented using MATLAB software and results are presented to verify merits of the scheme.